Living With Chronic Lower Pulmonary Disease - Charlotte Pooler (SAGE Publishing, 2014)
In this article, I present a phenomenological study of individuals' experiences of living with moderate to very severe chronic lower pulmonary disease (chronic obstructive pulmonary disease, asthma, or both). Phenomenology is a philosophy, distinct from descriptive or thematic research, which is useful as a foundation for scientific inquiry. In this study, I used the lens of Merleau-Ponty to understand and interpret participants' experiences of living with pulmonary disease, and the approach of van Manen for analysis. I conclude that in chronic pulmonary disease, awareness of breathing and the body is experienced in the sounds, sensations, and signals of breathing and the body, and in the experiences of the body-in-the-world. Central themes of being-in-the-world from the study describe the disruption of the embodied phenomenological self: Participants experienced slowing down, doing less, and having to stop due to shortness of breath. Both chronic and acute dyspnea were prevalent and the taken-for-granted aspects of daily activities were disrupted. Findings of this study have implications for public and patient education, and opportunities for integration of experiential aspects within nursing education and practice.